Adaptability and Acceptance of FinTech Payment System: A Studyon the Users of Bangladesh - Islam, Md Kamrul; Tamzid, Mohammad; Ocean, Muntasir Mamun (South Asian Journal of Social Sciences and Humanities, 2024)
With the global changes in financial activities due to FinTech, it impacts the financial behavior of  Bangladeshi users as well. Purposes: This study examines the customers’ attitude towards the  adaptation of fintech payment services in the context of Bangladesh. Method: A quantitative method is used in this study. Respondents were selected through a purposive sampling technique.  A survey technique is used to collect data about the variables. The respondents are the users of the  fintech payment system. Regression analysis was done to find out the relationship between  different variables. Main Findings: The research finds a statistically significant relationship between different variables which supports the theoretical framework. Applications: The findings  will allow for targeted interventions in promoting positive attitudes and intentions to facilitate the  adoption and sustained use of the systems.
Keywords: FinTech; Technology acceptance model (TAM); Payment system; Adaptability; Bangladesh